PRAKTIK TAMBU AEK DI WARUNG KOPI - Wahidan Nur; Ahmatnijar Ahmatnijar (Jurnal El-Thawalib, 2021)
Sale and purchase is an agreement made between the seller and the buyer. Every sale and purchase cannot be carried out in a false way and buying and selling must pay attention to the basic aspect, namely voluntary. The practice of buying and selling tea/coffee with the tambu aek system at the Coffee Shop is a habit of the people in Laru Bolak Village, Tambangan District, Mandailing Natal Regency. The practice of buying and selling carried out by the community is not clear about the size/measure of the object. So it is feared that it can harm one party. The problem in this study is how the practice of tambu aek at the Coffee Shop in Laru Bolak Village, Tambangan District, Mandailing Natal Regency and how the Compilation Review of Sharia Economic Law on the practice of tambu aek at the Coffee Shop in Laru Bolak Village, Tambangan District, Mandailing Natal Regency This type of research is field research, in which researchers go directly to the field to examine a problem. Sources of data used are primary data and secondary data. Methods of data collection using direct observation, interviews, and documentation.The results showed that the practice of buying and selling tea/coffee with the tambu aek system at the Coffee Shop in Laru Bolak Village, Tambangan District, Mandailing Natal Regency according to the Sharia Economic Law Compilation does not contain the element of gharar, because the object requirements are met. The practice of tambu aek is based on consensual consent without any element of coercion from any party. The implementation of the sale and purchase of tea/coffee with the tambu aek system at the Coffee Shop in Laru Bolak Village, Tambangan District, Mandailing Natal Regency is classified as a legal habit as long as no party feels disadvantaged, and the addition of hot water is something that is considered part of the tea/coffee consumed. on sale.